2018
DOI: 10.1080/03717453.2017.1415493
|View full text |Cite
|
Sign up to set email alerts
|

Mineralisation from hot fluid flows in the sandstone-type uranium deposit in the Kailu Basin, Northeast China

Abstract: The Qianjiadian-Baixingtu uranium deposit (QBUD) is in the post-Jurassic extensional Kailu basin of northeast China. There is a well-developed fault system in and adjacent to the deposit, and uranium mineralisation appears controlled by faults F 1, F 2, and F 3. Lots of diabase (dolerite) intrusions related to regional faults are extensive throughout the QBUD. The ellipsoidal and lenticular mineralised bodies in the QBUD conflict with the interlayered oxidation genesis. Furthermore, heat from the diabase intru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Nevertheless, recent EPMA chemical dating indicated that most of the U mineralization ages are younger than 40 Ma, with a peak in the Miocene or later (<20 Ma) [36], which is in good agreement with the tectonic evolution model proposed in the previous paragraph. Moreover, these ages postdate the emplacement of the mafic rocks, hence, arguing against the model proposed by Nie et al [34] involving mantle-derived CO 2 -rich hydrothermal fluids in the U ore genesis. with the tectonic evolution model proposed in the previous paragraph.…”
Section: Constraints On U Mineralizationmentioning
confidence: 59%
See 4 more Smart Citations
“…Nevertheless, recent EPMA chemical dating indicated that most of the U mineralization ages are younger than 40 Ma, with a peak in the Miocene or later (<20 Ma) [36], which is in good agreement with the tectonic evolution model proposed in the previous paragraph. Moreover, these ages postdate the emplacement of the mafic rocks, hence, arguing against the model proposed by Nie et al [34] involving mantle-derived CO 2 -rich hydrothermal fluids in the U ore genesis. with the tectonic evolution model proposed in the previous paragraph.…”
Section: Constraints On U Mineralizationmentioning
confidence: 59%
“…Eocene mafic rocks are widespread in sandstones of the Yaojia Formation hosting the U mineralization in the Qianjiadian deposit (Figure 1). Previous studies proposed that the intrusion of these mafic rocks triggered subsequent circulation of mantle-derived CO 2 -rich hydrothermal fluids, which could have been responsible for U leaching from the surrounding sandstones [34]. In addition, it has also been proposed that the genesis of the U mineralization in the Qianjiadian area was controlled by BSR processes within organic matter (OM)-bearing sandstones [28][29][30][31][32][33].…”
Section: Constraints On U Mineralizationmentioning
confidence: 99%
See 3 more Smart Citations